Sei sulla pagina 1di 49

 n N (x; µ, σ)

 χ 2

E E

E E

n r E P (E)

n

P (E) = lim

n→∞

r

X x i P i

P(X = x i ) = P i

i

P i = 1

X

x x f (x) x

f (x)dx = P (x X x + dx)

f (x)

f (x)dx = 1

A B P (A) P (B) A B A B P (A B) A B P (A B) A B

n AB A B P (A B) n A

¯

A B P (A B) n B B A

¯

¯

¯

P(B A) n 0 A B A B

N

P(A B) =

n

AB

N

P(B A) = n B

¯

N

N

P(A) = n AB + n A

¯

P(A B) = n A

N

P( A B) = n 0

N

¯

¯

P(B) = n AB + n B

N

P(A B) = n AB + n A + n B

N

n AB

P(A B) = n AB + n A

N

+ n AB + n B N

n

AB

N

= P (A) + P (B) P (A B)

A B

P (A|B) A B

P(A|B) = P(A B)

P(B)

P(A) = n AB + n A

N

P(B) = n AB + n B

N

A B

n

AB

n

AB

N

= P(A B)

P(B)

P(A|B) =

N

n AB + n B

n AB + n B

=

P(B|A) = P(A B)

P(A)

A B A B B A

P (A|B) = P (A)

P (A B) A B

P (A B) = P (A|B)P (B) = P (A)P (B)

P (A|B) = P (B|A) = 0 P (A B) = 0

X

 f (x)dx = P (x ≤ X ≤ x + dx) Ω f (x)dx = 1

f (x) f (x) F (x)

F(x) =

x

x

min

f(x )dx

x min x f (x) F (x) x [x min , x max ] x max x

F(x min ) = 0

F(x max ) = 1

f (x) F (x) x

x f (x)

x F (x)

g(x) x g(x) f (x) E[g(x)]

E[g(x)] = g(x)f (x)dx

f (x) g(x) E[a] = a a E g(x) g 1 (x) g 2 (x)

E[a 1 g 1 (x) + a 2 g 2 (x)] = a 1 E[g 1 (x)] +

a 2 E[g 2 (x)]

g(x) x g(x) f (x) V [g(x)]

V [g(x)] = E (g(x) E[g(x)]) 2

g(x) = x x µ

µ = E[x] = xf (x)dx

x σ 2

σ 2 = V [x] = E[(x µ) 2 ] = (x µ) 2 f (x)dx

σ x f (x) E

σ 2 = E[(x µ) 2 ] = E[x 2 + µ 2 2] = E[x 2 ] + µ 2 2µE[x]

= E[x 2 ] µ 2 = E[x 2 ] (E[x]) 2

g(x) = x k , f (x) µ k

µ 0 k = E[x k ] = x k f (x)dx

(xµ) k f (x)

µ k = E[(x µ) k ] = (x µ) k f (x)dx

µ

f (x) µ

γ 1 = µ 3

µ

3/2

2

γ 1 f (x) µ

γ 2 = µ 4 ) 2 3

(µ 2

n

x 1 , x 2 ,

, x n n

f(x 1 , x 2 ,

,

x n )dx 1 dx 2

dx n = 1

n x = (x 1 , x 2 ,

, x n )

f( x)d n x = 1

n x

 E[g( x)] = Ω g( x)f( x)d n x V [g( x)] = Ω (g( x) − E[g( x)]) 2 f( x)d n x

g( x) x i g( x) = x i x i

µ i = E[x i ] = x i f( x)d n x

V ( x) V ij

V ij

= E [(x i µ i )(x j µ j )]

= (x i µ i )(x j µ j )f( x)d n x

µ i µ j x i x j

V ij

V ii

i 2 x i

σ

σ

2

i

= V ii = E[(x i µ i ) 2 ] = (x i µ i ) 2 f( x)d n x

σ

2

i

= E[x

2

i

]

(E[x i ]) 2 .

V ij i

= j

x i x j cov(x i , x j )

(x i , x j ) = V ij = E[x i x j ] E[x i ]E[x j ]

(x i , x j ) = (x i

µ i )(x j µ j )f( x)d n x

= (x i x j µ i x j µ j x i µ i µ j ) f( x)d n x

= E[x i x j ] µ i x j f( x)d n x µ j x i f( x)d n x E[x i ]E[x j ]

= E[x i x j ] E[x i ]E[x j ] E[x j ]E[x i ] E[x i ]E[x j ]

= E[x i x j ] E[x i ]E[x j ]

ρ(x i , x j ) x i

f( x)d n x = 1

x j

ρ(x i , x j ) =

V ij

(x i , x j )

=

(V ii V jj )

1

2

σ i σ j

ρ

1 ρ(x i , x j ) 1

ρ = ±1 ρ = 0 y ij x x i x j

a y ij

y ij = x i + ax j

σ 2 (x i + ax j ) = σ

2

i

+

a 2 σ

2

j

+

2j (x i , x j )

σ

i 2 α = j i

σ 2 (x i + ax j )

σ

2

i

= 1 + α 2 + 2α (x i , x j )

σ i σ j

σ 2 (x i , x j )i σ j

α

1 + α 2 + 2αρ 0

ρ 2 1 0 ⇒ −1 ρ(x i , x j ) 1

n x 1 , x 2 ,

f ( x)

, x n

x i x j

f( x) = f 1 (x 1 )f 2 (x 2 )

f n (x n )

E[x i x j ] = x i x j f(x i , x j )dx i dx j = x i x j f i (x i )f j (x j )dx i dx j

= i x i f i (x i )dx i j x j f j (x j )dx j = E[x i ]E[x j ]

(x i , x j ) = E[x i x j ] E[x i ]E[x j ] = 0

ρ(x i , x j ) = 0.

x = (x 1 , x 2 ,

, x n ) n g( x)

g( x) =

n

i=1

a i x i

a i g( x)

E

n

i=1

a i x i =

n

i=1

E[a i x i ] =

n

i=1

a i µ i

E

V

n

i=1

a i x i

= E

n

i=1

a i x i E

n

i=1

a i x i 2

= E

 n n i=1 a i x i − i=1 n i,j=1  a i µ i 2   = E  n i=1  a i (x i − µ i ) 2   a i a j (x i − µ i )(x j − µ j )   = E  n n  = E  a 2 i (x i − µ i ) 2 + a i a j (x i − µ i )(x j − µ j )   i=1 i =j

E

V

n

i=1

a i x i =

n

i=1

a

2

i

E

(x i µ i ) 2 +

=

n

a i a j E[(x i µ i )(x j µ j )]

i

=j

n n

i=1

a

2

i

σ

2

i

+

i

=j

a i a j (x i , x j )d

i 2

a i a j